2013
DOI: 10.5935/0103-507x.20130043
|View full text |Cite
|
Sign up to set email alerts
|

Manual hyperinflation in airway clearance in pediatric patients: a systematic review

Abstract: ObjectiveTo perform an assessment of the available literature on manual hyperinflation as a respiratory physical therapy technique used in pediatric patients, with the main outcome of achieving airway clearance. MethodsWe reviewed articles included in the Lilacs (Latin American and Caribbean Literature on Health Sciences/Literatura Latino Americana e do Caribe em Ciências da Saúde), Cochrane Library, Medline (via Virtual Health Library and PubMed), SciELO (Scientific Electronic Library), and PEDro (Physiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 16 publications
(16 reference statements)
0
23
0
2
Order By: Relevance
“…MHI is a treatment technique commonly used by physical therapists in intensive care units for passive lung inflation, intensification of elastic recoil forces, enhancement of the peak expiratory flow, and consequent clearance of secretions accumulated in the airways [20]. According to Ambrozin et al [21], MHI consists of slow deep inspirations, followed by an inspiratory hold and a quick pressure release using a manual resuscitation bag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MHI is a treatment technique commonly used by physical therapists in intensive care units for passive lung inflation, intensification of elastic recoil forces, enhancement of the peak expiratory flow, and consequent clearance of secretions accumulated in the airways [20]. According to Ambrozin et al [21], MHI consists of slow deep inspirations, followed by an inspiratory hold and a quick pressure release using a manual resuscitation bag.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MHI in pediatric patients seems to be useful to clear the airways of children with acute respiratory failure or in recovery following heart congenital disease and upper abdominal surgery, bone marrow transplantation, asthma, tracheal reconstruction, brain injury, airway injury, and heterogeneous lung diseases. This technique increases spontaneous tidal volume and improves chest x-ray appearance and the oxygenation index (PaO2 / FiO2) [20]. As regards the monitoring of passive pulmonary mechanics in infants, obtained by complete relaxation of the respiratory muscles after the use of respiratory techniques such as HMI, it is necessary to induce the Hering-Breuer reflex, triggered by the rapid obstruction of the airway (for 1 second) at the end of normal inspiration to compare the improvement achieved with the technique [29].…”
Section: Discussionmentioning
confidence: 99%
“…As manobras de higiene brônquica ou manobras desobstrutivas, favorecem o deslocamento das secreções e a subida para regiões mais externas dos pulmões por meio do aumento do fluxo expiratório, promovendo a tosse e deslocando as secreções 6,7 . Quando a tosse é ineficiente ou na presença de tubo endotraqueal a aspiração de secreções se faz necessária e finaliza o processo de remoção das secreções mobilizadas com o uso dessa técnica 8,9 .…”
Section: Expressão De Dor Após Atendimento De Fisioterapia Em Recémnaunclassified
“…Physiotherapists working in adult intensive care units often use manual hyperinflation techniques in conjunction with other manipulations to expand the lung and loosen secretions, and in some centers the technique is commonly used for critically ill children and infants as well. [79][80][81][82] Manual hyperinflation usually consists of a series of deep manual inflations (ideally to a predetermined set pressure or volume) with brief inspiratory holds, followed by a rapid release of the bag to enhance expiratory flow. 2 Manual hyperinflation aims to prevent or treat lung collapse, improve oxygenation and compliance, and promote secretion clearance.…”
Section: Manual Hyperinflationmentioning
confidence: 99%
“…Only three studies relating to manual hyperinflation in children were identified for inclusion in a systematic review: two observational studies and one randomized crossover trial. 76,82,87 The crossover trial did not analyze different CPT modalities separately and therefore no conclusions can be made regarding the effects of manual hyperinflation itself. 7 Therefore, there is insufficient evidence regarding the safety or efficacy of manual hyperinflation in critically ill infants and children and there are reasons for concern for implementing this modality in this population, as outlined further later.…”
Section: Manual Hyperinflationmentioning
confidence: 99%